Severe Anxiety Post-COVID-19 Infection. (1st December 2021) - Driscoll, Maggie; Gu, Jason
Abstract : COVID-19 infection is linked to increased risk of neuropsychiatric symptoms such as psychosis and suicidal ideation/behavior. After further review of the literature, there is not a large body of data on anxiety following COVID-19 infection. Most literature found is related to fear/anxiety of contracting and dying from COVID-19. We illustrate a case of a 27-year-old male with no previous psychiatric treatment history or symptomology, who developed severe anxiety with intrusive thoughts of self-harm via firearm after COVID-19 infection. Given the severe nature of the anxiety and intrusive thoughts, the patient feared for his safety and sought acute inpatient admission. The patient was effectively treated with group therapy and psychotropic medications and was able to be discharged in a timely manner with outpatient psychiatric follow-up. Much is still unknown of COVID-19. With this case report, we discuss a potential relationship between anxiety and COVID-19 infection.